Structural, electrical, thermal and optical properties of polycrystalline metal chalcogenide compounds - Liew, Josephine Ying Chyi (2011)
Copper selenide (CuSe), tin selenide (SnSe) and copper tin selenide (Cu2SnSe3)powder were synthesized by chemical precipitation technique. The concentration,pH, complexing agent, synthesis time and temperature have been optimized to produce very pure CuSe, SnSe and Cu2SnSe3 compounds. The optimum condition to prepare CuSe compound was 0.03 mol CuCl22H2O with 0.05 mol Se concentration, SnSe compound was 0.08 – 0.09 mol of SnCl2 prepared in 0.06 mol tartaric acid with Se concentration maintained constant at 0.03 mol, and Cu2SnSe3 compound was 0.068 mol CuCl22H2O, 0.078 mol SnCl2·2H2O and 0.025 mol Se concentration with the solution of pH at 1.30. The structural, compositional, morphological, electrical and thermal properties of the synthesized compounds have been carried out by X-ray diffraction analysis (XRD), energy dispersive X-ray (EDX) analysis, Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM), four point probe and van der Pauw technique, and Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC) and photoflash technique respectively. Information on the structure and morphology of the synthesized CuSe, SnSe and Cu2SnSe3 powder such as the XRD patterns, structural stability, phase transformation, mean crystallite size, compositions, shape of particles and particle size play an important role in understanding and explaining the temperature dependence of its electrical and thermal properties. The observed variation in thermal diffusivity for CuSe was (1.20  0.02)  10-2  (6.01  0.02)  10-3 cm2/s,SnSe was (3.80  0.08)  10 -3  (1.60  0.01)  10 -3 cm2/s and Cu2SnSe3 was (4.31  0.09)  10-3  (2.97  0.03)  10-3 cm2/s. All of the systems displayed similar type of behavior where the thermal diffusivity of the powder decrease exponentially as the temperature increased. Analysis of the data showed the response was ably explained by the phonon scattering mechanisms. The intrinsic and extrinsic scattering at different temperature regions of the synthesized CuSe, SnSe and Cu2SnSe3 compound was distinguished through thermal diffusivity and mobility measurement as a function of temperature. The variation of the electrical conductivity in the CuSe was between (8.24  0.02)  102 to (10.30  0.04)  102 S/cm, SnSe was between (15.97  0.06) 10-4 to (2.25  0.04) S/cm and Cu2SnSe3 was between (5.04  0.01)  102 to (7.32  0.03)  102 S/cm. The high temperature region showed characteristics of thermionic emission while the variable range hopping was the main mechanism in the lower temperature region. Single layer and multilayer thin films of CuSe, SnSe and Cu2SnSe3 were physically deposited on glass substrate through thermal evaporation technique using powder that was synthesized from chemical precipitation technique. Various film properties,including the thickness, structure, composition, morphology, surface roughness,average grain size, electrical conductivity, Hall mobility, carrier sheet density,optical band gap and refractive index were studied and discussed in details. The results obtained showed that the physical properties such as the electrical conductivity for CuSe film ((2.72  0.03)  103  (61.05  0.03)  102) S/cm), SnSe film ((0.38  0.01)  10-2 – (1.08  0.03)  10-1 S/cm) and Cu2SnSe3 film ((7.93  0.01)  101  (41.48  0.06)  102 S/cm), reflective indices for CuSe film ((1.468  0.003) – (3.355  0.008)), SnSe film ((0.994  0.001)  (2.551 0.001)) and Cu2SnSe3 film ((1.569  0.001)  (3.473  0.001)), and optical band gap for CuSe film ((1.83  0.04)  (2.58  0.06)), SnSe film ((0.99  0.01)  (2.45  0.08)) and Cu2SnSe3 film ((1.83  0.05)  (2.37  0.01)) were significantly influenced by the thickness (140 – 950 nm), annealing temperature (300 – 673 K) and preparation condition (single layer and multilayer deposition process). Finally, considering the optimization properties of the thin film, multilayer Cu2SnSe3 film annealed at temperature below 573 K with thickness not less than 1 m has been proposed as the most suitable film to be used in photovoltaic devices.